Nepal Medical Council: The past and the future - Dixit, H (Kathmandu University Medical Journal, 2010)
The Nepal Medical Council (NMC) has been technically in operation for forty six years though in reality it is much less. The initial years were spent in establishing it. It is only in the last fifteen years or so that there has been much interest in it's functioning. The objective of the NMC is to protect the public and also to oversee the medical education being conducted within the country. A brief account of the NMC from its date of establishment till the present is given here. Key words: NMC; NMA; Medical Education; Medical Colleges. DOI: 10.3126/kumj.v7i3.2723 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 196-203